Expression of AT1R, AT2R and AT4R and their roles in extravillous trophoblast invasion in the human - Williams, P.J.; Mistry, H.D.; Innes, B.A.; Bulmer, J.N.; Broughton Pipkin, Fiona (Elsevier, 2010)
The placental renin-angiotensin system (RAS) is active from early pregnancy and may have a role in placentation. Angiotensin II (AngII) acts via binding to receptor types AT1R and AT2R. Recently smaller peptide members of the angiotensin family have been recognised as having biological relevance. Angiotensin (3-8) (AngIV) has a specific receptor (AT4R) and evokes hypertrophy, vasodilatation and vascular inflammatory response. The aim of this study was to characterise placental expression of AT1R, AT2R and AT4R, and to determine whether AngII and AngIV regulate extravillous trophoblast (EVT) invasion, apoptosis and proliferation. Placental samples were obtained from women undergoing elective surgical termination of pregnancy (TOP) at 8-10 weeks gestation (early TOP), 12-14 weeks gestation (mid TOP) or at delivery following normal pregnancy or with pre-eclampsia (PE). Immunohistochemistry and qRT-PCR were performed to determine placental mRNA and protein expression of AT1R, AT2R and AT4R was done at all gestational ages. EVT invasion following culture with AngII or AngIV was assessed in early placental tissue using Matrigel invasion assays. Invasion was assessed on day 6 of culture and placental explants were harvested for immunohistochemical analysis of apoptosis and proliferation. The results from qRT-PCR and immunohistochemistry showed placental AT1R expression which did not vary with gestation. The highest levels of expression of AT2R were found in early and mid TOP placentae compared to term pregnancy. Expression of AT4R was increased in term placentae, with a significant reduction in PE placentae. Moreover, culture with AngIV or AngII increased EVT invasion from placental explants, which showed increased trophoblast proliferation and reduced apoptosis. This study has characterised expression of AT4R and AT1R and AT2R in human placenta throughout normal pregnancy and in PE. Both AngIV and AngII may play an important role in normal pregnancy.